Perlawanan Rakyat dan Kriminalisasi Gerakan Sosial: Studi Kasus Konflik Peternakan di Cibetus Padarincang - Nawawi, Taosyekh; Amalia, Aam; Fakhrudin, Irfan; Sujana, Ahmad Maftuh (Universitas Syiah Kuala, 2025)
This study examines the dynamics of social resistance and criminalization in the case of a large-scale poultry farm development in Cibetus, Padarincang, Serang, Banten. The research highlights how the implementation of development projects without adequate consultation and community consent has triggered conflicts related to environmental degradation, public health, and the right to a safe living space. Using a qualitative case study approach, data were collected through semi-structured interviews with affected residents, community leaders, and civil society organizations, as well as through documentation analysis and field observations. The findings reveal that the local community responded to the project through various forms of organized resistance, including peaceful protests, public advocacy, legal actions, and direct confrontation. These actions were met with repressive state responses, including the arrest and prosecution of residents without proper legal procedures. The criminalization of citizens involved in the resistance underscores a broader pattern of structural injustice, where legal instruments are used to suppress civic participation and protect corporate interests. This study concludes that the conflict in Cibetus reflects a deeper imbalance in power relations between the state, corporations, and civil society. The resistance demonstrated by the community is not merely an objection to a development project but a demand for justice, recognition, and the protection of fundamental rights. The research emphasizes the need for inclusive and participatory governance that respects environmental and social rights in the planning and implementation of development policies.